Evidence-based decision making: How "Sully" Sullenberger saved 155 passengers with 40 years of practice - Rousseau, Denise M. (Henry Stewart Talks, 2019)
This case study looks at the experience of Chesley ‘Sully’ Sullenberger who successfully landed an aeroplane carrying 155 passengers on crew on the Hudson river after it was hit by a flock of birds. It shows that neither luck or genius enabled the pilot to land calmly and safely, but rather decades of deliberate practice.